THE AUTHORITY OF THE AHAD HADITH IN AQIDAH (The Study of Nashirudin Al-Bani's Thought) - Ahmad Zumaro (Akademika : Jurnal Pemikiran Islam, 2022)
Hadiths are divided into Mutawatir and Ahad. The Mutawatir refers to the Hadith of qot'ul al-wurud or the hadith that is believed to be true, while the Ahad refers to zhon al-wurud in which its authenticity is still questioned as the cornerstone of Islamic Aqidah (creed). The purpose of this study is to find out the thoughts of Al-Bani on the authority of the Ahad Hadith as the basis of Aqidah. The method used in this study was library research with a content analysis approach. The results of the study revealed that the Hadith al-Ahad can be employed as the foundation of Aqidah when it meets the requirements of the Hadith’s authenticity. The condition of the Hadith's authenticity is that the sanad (chain of narrators) must be continually reported by the narrators (Rowi), whose agreement upon a lie is impossible (tsiqoh), and who are exempt from illah and syadz characteristics. Ahad Hadith which has been investigated and proven to be authentic (shahih Hadith) will be classified as qothil al-wurud rather than zhon al-wurud. Thus, Ahad Hadith can be employed as a foundation for Aqidah. The narration of Ahad Hadith is considered bid'ah because it was not carried out by the Prophet SAW and his companions. Keywords: Al-Bani, Hadith al-Ahad, Aqidah